Evidence that LDL receptor-related protein 1 acts as an early injury detection receptor and activates c-Jun in Schwann cells. Issue 18 (14th December 2016) - Flütsch, Andreas; Henry, Kenneth; Mantuano, Elisabetta; Lam, Michael S.; Shibayama, Masataka; Takahashi, Kazuhisa; Gonias, Steven L.; Campana, Wendy M.
Abstract : Schwann cells (SCs) detect injury to peripheral nerves and transform phenotypically to respond to injury and facilitate repair. Cell-signaling pathways and changes in gene expression that drive SC phenotypic transformation in injury have been described; however, the SC receptors that detect peripheral nervous system (PNS) injury have not been identified. LDL receptor-related protein 1 (LRP1) is a receptor for numerous ligands, including intracellular proteins released by injured cells and protein components of degenerated myelin. In certain cell types, including SCs, LRP1 is a cell-signaling receptor. Here, we show that binding of the LRP1 ligand, tissue-type plasminogen activator (tPA), to cultured rat SCs induces c-Jun phosphorylation, a central event in activation of the SC repair program. The response to tPA was blocked by the LRP1 antagonist, receptor-associated protein. c-Jun phosphorylation was also observed when cultured rat SCs were treated with a recombinant derivative of matrix metalloproteinase-9 that contains the LRP1 recognition motif (PEX). The ability of LRP1 to induce c-Jun phosphorylation and ERK1/2 activation was confirmed using cultures of human SCs. When tPA or PEX was injected directly into crush-injured rat sciatic nerves, c-Jun phosphorylation and ERK1/2 activation were observed in SCs in vivo . The ability of LRP1 to bind proteins released in the earliest stages of PNS injury and to induce c-Jun phosphorylation support a model in which SC LRP1 functions as an injury-detection receptor in the PNS.